2015
DOI: 10.1126/science.aaa6111
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of hierarchical protein dynamics

Abstract: A hierarchy of protein motions Functioning proteins are not static but explore complex conformational energy landscapes. Lewandowski et al. used multinuclear solid-state nuclear magnetic resonance experiments to measure protein motion over a broad range of temperatures and time scales. Above 160 K there was a strong coupling between solvent and protein motion. The hierarchy of motions as the temperature increased revealed the dynamic modes that relate solvent, sid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
313
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 244 publications
(328 citation statements)
references
References 75 publications
15
313
0
Order By: Relevance
“…In variable temperature 1 H and 13 C MAS ssNMR measurements we detected the temperatures at which the solvent froze and the liquid-to-gel transition of the lipids occurred. In line with earlier MAS ssNMR studies (40)(41)(42)(43), the aqueous solvent (20 mM HEPES buffer at pH 7.4) froze at temperatures significantly lower than 0 C. This effect stems from the reduced length scales of water pockets in the sample, compared with bulk water that freezes at 0 C (see Discussion). To our surprise, we also noted a substantial lowering of the lipid phase transition.…”
Section: Mas Nmr Probing Of Solvents and Lipid Dynamicssupporting
confidence: 83%
See 1 more Smart Citation
“…In variable temperature 1 H and 13 C MAS ssNMR measurements we detected the temperatures at which the solvent froze and the liquid-to-gel transition of the lipids occurred. In line with earlier MAS ssNMR studies (40)(41)(42)(43), the aqueous solvent (20 mM HEPES buffer at pH 7.4) froze at temperatures significantly lower than 0 C. This effect stems from the reduced length scales of water pockets in the sample, compared with bulk water that freezes at 0 C (see Discussion). To our surprise, we also noted a substantial lowering of the lipid phase transition.…”
Section: Mas Nmr Probing Of Solvents and Lipid Dynamicssupporting
confidence: 83%
“…2 C), the water peak moves (in accordance to the known temperature dependence of water 1 H shifts (35,36)), but remains intense and narrow. Thus, the water remains unfrozen even at À9 C. As is discussed in more detail below, this kind of solvent freezing point depression is typically seen for densely packed MAS ssNMR samples (29,42,43). Consistent with the T m values of the DOPC and TOCL lipids, which are well below 0 C (Fig.…”
Section: Phase Changes In Monounsaturated Mixed-lipid Vesiclessupporting
confidence: 64%
“…Typically, X-ray crystallographic data are measured from crystals maintained at 100 K in order to immobilize X-raygenerated free radicals and damaged protein and minimize radiation damage, leading an increase in crystal lifetime of up to two orders of magnitude relative to RT (Southworth-Davies et al, 2007). Between RT and 100 K, protein crystals undergo at least one and possibly several temperature-dependent transitions (Weik & Colletier, 2010;Lewandowski et al, 2015;Ringe & Petsko, 2003;Keedy et al, 2015). Notably, anharmonic macromolecular motions resume above the glass transition that occurs in the range 180-220 K, where solvent viscosity is greatly reduced.…”
Section: Introductionmentioning
confidence: 99%
“…However, the barriers need to be small to make their crossing possible at physiological temperature, as the dynamics are "fueled" by the thermal fluctuations of the surrounding liquid. [20,21] Experimentally it has been observed that upon binding the loss in entropy of the protein, which would oppose the reaction, is often paired to the emergence of disorder in remote regions of the protein, apparently uncorrelated to the binding site. [19] New flexible regions often arise in the relaxed bound state, or exposed hydrophobic residues are found to transition to the hydrophobic region, becoming protected and increasing the entropy of the solvent in the well-known mechanism of enthalpy-entropy compensation.…”
Section: Introductionmentioning
confidence: 99%